SOME NEW REMAINS OF TRAGULIDAE (MAMMALIA: RUMINANTIA) FROM THE MIDDLE SIWALIKS OF PAKISTAN - M. Asim; M. A. Babar; K. Aftab; M. A. Khan; S. G. Abbas; R. Shahid; M. K. Nawaz; M. Akhtar (Journal of Animal and Plant Sciences, 2019)
New tragulid fossils were collected from the Late Miocene sites of Potwar Plateau in the Punjab province, Pakistan. The studied sites include the classical localities of Dhok Pathan and Nagri from Chakwal district and Padhri from Jhelum district, Punjab, Pakistan. The material belongs to two tragulid species Dorcatherium majus and D. minus. This paper presents the dental material of both species from the Siwalik Group of Pakistan.
Keywords: Taxonomy; Dorcatherium; Miocene; Pliocene; Palaeontology